MEDIA EXPLORATION AS PRODUCT DEVELOPMENT OF OBI BELT PAINTINGS AT AGUNG BALI COLLECTION: Eksplorasi Media Sebagai Pengembangan Produk Obi Belt Lukis Di Agung Bali Collection - Toganata, I Made Anju Adi; Sucipta, I Wayan Adi; Budiaprilliana, Luh (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
This internship/practical work program is implemented to provide opportunities for students to choose their interests and prepare students to enter the world of work. Obi belt is a textile product from Japan that is used as a belt to keep the kimono neat and tight. Product development is a strategy and process used by companies to create new products, improve old products, or increase the usefulness of products to existing market segments on the assumption that customers want new elements about these products. The purpose of this internship is to identify the strategy and process of product development at Agung Bali Collection. The method of implementation in this MBKM Internship / Work Experience Program students will be involved in various practical activities, such as direct observation of the fabric weaving process, how to design fabric designs and techniques used in the manufacture of woven fabrics and also need to know how the marketing system is carried out in the industry at Agung Bali Collection. Data collection used to find information and data in this internship is through interview, observation or observation, documentation and literature. The results of the MBKM internship program are in the form of knowledge, skills and technology transfer. The principles of knowledge, skill and technology transfer can lead to new innovations in obi belt products. The products made by Obi Belt are unique, special and certainly different from other products on the market. The transfer of knowledge, skills and technology gained at Agung Bali Collection greatly facilitates the creation of new innovations in obi belts.